تحليل العمل المفهوم، الطرق والاستخدامات - صباح, د/ غربي (Sciences humaines; Vol. 39 (2015): SCIENCES HUMAINES (Mars), 2015)
إذا كانت معظم الأعمال تطورت تقنياتها وتعقدت طرق تشغيلها، فإن الحاجة لتحليل العمل تصبح ماسة عن ذي قبل لكي نستطيع أن نحدد المتطلبات البشرية، وبتحليل ديناميات تحليل العمل نجد أنه يسهم في نقل التكنولوجيا ويعمل على تطويرها، كما يساعد على تجنب المشكلات الملازمة لدخول التكنولوجيا الحديثة، ولهذه الاعتبارات وجب دراسة تحليل العمل والاهتمام به.    وقد جاء هذا المقال ليتناول بشيء من التفصيل تعريف تحليل العمل والمفاهيم المتداخلة معه ثم الإشارة لاستخداماته وأهدافه والأساليب والفنيات التي يعتمد عليها في جمع البيانات، ثم الإشارة إلى أنواعه، وأخيرا نشير إلى علاقته بتصميم العمل . If most of the work has evolved technologies and complicated methods of operation , the need to analysis the job becomes urgent than ever before so that we can determine human requirements , and analysis the dynamics of the job analysis, we find that it contributes to the transfer of technology and works to develop , and helps to avoid the problems inherent in the entry of modern technology, but  these considerations should study analysis work and interest .    Came to this article examines in some detail the analysis of the definition of work and overlapping concepts with him and then uses the signal to the objectives and the methods and techniques that depend on them for data collection , and then refer to types , and finally point out the relationship with the design work